164k views
5 votes
The gravitational force between two asteroids is 2.59 × 10 (exponent)-6 N. The centers of mass are 2000 meters away and their masses are equal. What is the mass of each asteroid?​

1 Answer

4 votes

Answer:


2.79 * 10^5 \ \text{kg}

Step-by-step explanation:

Newton's Law of Universal Gravitation:


  • $F= G(m_1 m_2)/(r^2)
  • F = force of gravity (N)
  • G = gravitational constant
    (6.67 * 10^-^1^1 \ N(m^2)/(kg^2))

  • m_1 = mass of Object 1 (kg)

  • m_2 = mass of Object 2 (kg)
  • r = distance between the center of mass (m)

Let's convert our given information to scientific notation:


  • 2000 \ m \rightarrow 2.0 * 10^3 \ m

Now using the gravitational force and the distance between centers of mass that are given, we can plug these into Newton's law:


  • 2.59 * 10^-^6 $\ N = 6.67 * 10^-^1^1 \ N (m^2)/(kg^2) * (m_1 m_2)/((2.0 * 10^3 \ m)^2)

Remove the units for better readability.


  • 2.59 * 10^-^6=6.67 * 10^-^1^1 (m_1m_2)/((2.0 * 10^3)^2)

Divide both sides of the equation by the gravitational constant G.


  • (2.59 * 10^-^6)/(6.67 * 10^-^1^1) =(m_1m_2)/((2.0 * 10^3)^2)

Distribute the power of 2 inside the parentheses.


  • (2.59 * 10^-^6)/(6.67 * 10^-^1^1) =(m_1m_2)/(2.0 * 10^6)

If we evaluate the left side of the equation, we get:


  • 3.88305847 * 10^4 = (m_1m_2)/(2.0 * 10^6)

Multiply both sides of the equation by r.


  • 7.76611694 * 10^1^0= m_1m_2

In order to find the mass of one asteroid, we can use the fact that both asteroids have the same mass, therefore, we can rewrite
m_1m_2 as
m^2.


  • 7.76611694 * 10^1^0= m^2

Square root both sides of the equation.


  • m=√(7.76611694 * 10^1^0)

  • m=2.78677536 * 10^5

  • m=2.79 * 10^5

Since m is in units of kg, we can state that the mass of each asteroid is 2.79 * 10⁵ kg.

User Tenor
by
5.1k points